1936
DOI: 10.1085/jgp.20.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evaluation of Sieve Constants in Ultrafiltration

Abstract: The partial retention of the disperse phase in the ultrafiltration of a monodisperse system through an isoporous filter is interpreted on a statistical basis, and a simple expression for the sieve constant is evaluated in terms of the calibrated membrane porosity and the particle size. Curves calculated from this expression are in reasonable agreement with experimental data for the ultrafiltration of serum albumin, hemocyanin (Helix), and foot-and-mouth disease virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1
1

Year Published

1962
1962
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(94 citation statements)
references
References 11 publications
1
91
1
1
Order By: Relevance
“…For the case of uncharged solutes , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 -5-only purely steric effects determine this ratio, which coincides with the steric partitioning coefficient. Assuming that flow through a membrane takes place along the x-axis direction, being x=0 and x=∆x the coordinates for the interfaces, and denoting by -and + the left and right sides of each interface, the membrane partition coefficient [19,20] is:…”
Section: Membrane Partition Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of uncharged solutes , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 -5-only purely steric effects determine this ratio, which coincides with the steric partitioning coefficient. Assuming that flow through a membrane takes place along the x-axis direction, being x=0 and x=∆x the coordinates for the interfaces, and denoting by -and + the left and right sides of each interface, the membrane partition coefficient [19,20] is:…”
Section: Membrane Partition Coefficientmentioning
confidence: 99%
“…Different correlations have been proposed in the literature for the hindrance factors [19,22,23]. Dechadilok and Deen [21], in addition to analyzing some of these proposals, study and present a way of introducing the effect of pressure gradient in theses hindrance factors.…”
Section: Transport Equationmentioning
confidence: 99%
“…Ibackstedt et a!. [18] (1993) used the LG method to study dynamic (frequency-dependent) permeability of a porous medium, a notoriously difficult problem, because one has to obtain the frequency-dependent permeability by Fourier-transforming the numerical results. Normally, LG results are subject to relatively large noise and fluctuations, and therefore their Fourier transform is very difficult to obtain.…”
Section: Lattice-gas Simulationmentioning
confidence: 99%
“…Despite this, Knackstedt et al [18] showed, by reproducing the exact results for the dynamic permeability of channel-like systems, that if a large number of realizations are used, the LG results are reliable. This indicates the reliability of LGA for simulating flow problems.…”
Section: Lattice-gas Simulationmentioning
confidence: 99%
“…Desde hace mucho tiempo se han invertido esfuerzos para esclarecer la selectividad de las membranas porosas usando modelos hidrodinámicos de transporte impedido [85]. En los años 30 Ferry ya desarrolló estudios muy influyentes de los que se derivan factores de impedimento para el transporte convectivo a partir de consideraciones estéricas [86]. En estos estudios se relaciona la retención con los radios medios de las moléculas y de los poros de la membrana y se describe relativamente bien las variaciones de retención con el tamaño o la masa molar de las moléculas.…”
Section: Mecanismos De Transporte a Través De Una Membrana De Nanofilunclassified